QIROAH FII AAFAAQ MUSHTHALAHAY AL-THAB’I WA AL-SHAN’I FII AL-NAQD AL-’ARABY AL-QADIIM - al-Dakeel, Muhammad Majid (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2011)
Seemingly, the classic Arab criticism experienced terminology crisis. Besides the word-meaning balance, our critics seized upon dichotomization in the poetry theory, with many arguments were about the two terms of (tab') temper and (takaluf) pretense with no specific meaning being given to each. Our classic critics have been using multiple terms to suggest such dichotomy. For example, to indicate improved and cultured poetry, they have been using such terms as (takaluf, sana'a, mataskalaf, matakalif, sani'). However, for term temper our classic critics typically used numerous synonymous words which, in fact, indicated the same meaning. Such terms as temper, innate, genius, talent, disposition, wittiness, and intuition are all represent poetical faculty, or poetical energy of a poet. Despite diversified, such dichotomous criticism terms are synonymous; a poet, for instance, should already have the inspiration and poetical faculty in order to compose poetry. Only then and next to temper comes assuming (sana'a) and pretending (takaluf) by a poet in an effort to produce improved and reviewed poetry which reflect development of a community.Keywords: Mushthalahah, Thab’i, Shan’i , Naqd